2020
DOI: 10.1186/s40814-020-00672-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a televideo physical activity and nutrition program for recent kidney transplant recipients

Abstract: Background Post-transplant weight gain affects 50–90% of kidney transplant recipients adversely affecting survival, quality of life, and risk for diabetes and cardiovascular disease. Diet modification and physical activity may help prevent post-transplant weight gain. Methods for effective implementation of these lifestyle modifications are needed. The objective of this study is to assess the feasibility and acceptability of a remotely delivered nutrition and physical activity intervention amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 37 publications
(38 reference statements)
2
31
0
Order By: Relevance
“…Six studies reported body weight only [39,41,44,47,48,50], four reported BMI [43,45,49,51], and six reported both body weight and BMI [36,42,43,46,52,53] post-intervention. Seven out of the sixteen studies recorded body weight or BMI at an interim time point of three to six months, and at a one-year follow-up [36,39,45,49,50,52,54].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies reported body weight only [39,41,44,47,48,50], four reported BMI [43,45,49,51], and six reported both body weight and BMI [36,42,43,46,52,53] post-intervention. Seven out of the sixteen studies recorded body weight or BMI at an interim time point of three to six months, and at a one-year follow-up [36,39,45,49,50,52,54].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Methodological variation was evident across the ten RCTs included in this systematic review and meta-analysis. One study included a 12-month diet only intervention [45], three studies [36,39,46] included exercise only interventions ranging from three to twelve months, and six RCTs included combined interventions [43,44,48,49,53,54]. The RCTs with combined interventions varied significantly in duration between fourteen weeks [44], six months [48,53], eight months [43], and one year [49,54].…”
Section: Characteristics Of Interventionsmentioning
confidence: 99%
See 3 more Smart Citations